The many faces of parasite calreticulin - Esperante, Diego; Flisser, Ana; Mendlovic, Fela (Frontiers in Immunology, 2023)
Calreticulin from parasites and its vertebrate hosts share ~50% identity and many of its functions are equally conserved. However, the existing amino acid differences can affect its biological performance. Calreticulin plays an important role in Ca++ homeostasis and as a chaperone involved in the correct folding of proteins within the endoplasmic reticulum. Outside the endoplasmic reticulum, calreticulin is involved in several immunological functions such as complement inhibition, enhancement of efferocytosis, and immune upregulation or inhibition. Several parasite calreticulins have been shown to limit immune responses and promote infectivity, while others are strong immunogens and have been used for the development of potential vaccines that limit parasite growth. Furthermore, calreticulin is essential in the dialogue between parasites and hosts, inducing Th1, Th2 or regulatory responses in a species-specific manner. In addition, calreticulin participates as initiator of endoplasmic reticulum stress in tumor cells and promotion of immunogenic cell death and removal by macrophages. Direct anti-tumoral activity has also been reported. The highly immunogenic and pleiotropic nature of parasite calreticulins, either as positive or negative regulators of the immune response, render these proteins as valuable tools to modulate immunopathologies and autoimmune disorders, as well as a potential treatment of neoplasms. Moreover, the disparities in the amino acid composition of parasite calreticulins might provide subtle variations in the mechanisms of action that could provide advantages as therapeutic tools. Here, we review the immunological roles of parasite calreticulins and discuss possible beneficial applications.